Literature Review: Influence Learning Entrepreneurship to Green Entrepreneurial Intention - Poy Saefullah Zevender; Mahfud Muziburrohman (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This literature review study is in the background with the existence of empirical phenomena that describe development business impactful entrepreneurship. Negatively, the concept of green economy can be used to minimize these negative impacts. It can happen with the existence of green entrepreneurial intention or desire for good and healthy entrepreneurship without damaging the environment. This needs driving action, like learning entrepreneurship, because still many people don't understand the green economy and green entrepreneurial intentions. Study methods and literature This was done for four articles obtained from Google Scholar. The result of the study literature review is that learning entrepreneurship can influence green entrepreneurial intention with encouragement factors recognizing opportunities, innovations, and risk-taking.